PENGARUH PRAKTIK SPIRITUAL DZIKIR DAN SHALAWAT TERHADAP PENINGKATAN KOGNITIF DAN PRODUKTIVITAS BERPIKIR - Mohammad Ali Mahfud; Fuad Fansuri; Muhammad Yusuf Qardlawi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study explores the impact of dzikir (remembrance of Allah) and shalawat (blessings upon the Prophet Muhammad) on a person's mindset, focusing on their effects as spiritual therapies and their influence on productive thinking. Through an Islamic philosophical and psychological perspective, it discusses how these practices contribute to inner peace, mental clarity, and improved cognitive functioning. Dzikir is identified as a tool for spiritual purification that enhances focus, reduces anxiety, and leads to a more positive mental state. It also facilitates access to deeper knowledge (ma'rifah) and helps reconcile the rational mind with the heart. The philosophical view highlights dzikir as an epistemological means to attain higher truths beyond the physical realm, serving as a bridge to divine wisdom. In conclusion, dzikir and shalawat promote both psychological well-being and intellectual growth by nurturing a calm, reflective mindset, leading to enhanced productivity in both personal and academic life.